Wacana Kritis Kontribusi Sosial Politik Legislator Perempuan Aceh terhadap Perempuan Aceh - Alwi; Fauzi (Universitas Andalas, 2026)
The role of Acehnese female legislators is crucial for empowering and advocating for women's socio-political wellbeing in Aceh. Their social orientation skills often allow them to effectively prioritize women's rights and social equity over their male counterparts. However, their low electability in the 2024 elections poses significant challenges to addressing the pressing needs of Acehnese women. This study uses qualitative methods, including library research and field observations, to analyze their roles. Findings indicate that while these legislators are important for advancing women's interests, their contributions are hindered by internal obstacles such as insufficient political and legal competencies, and external issues like entrenched power dynamics and cultural norms. Political parties often exacerbate these barriers, limiting female legislators' effectiveness. The research underscores the need to enhance knowledge based on Acehnese norms and improve the leadership skills of female legislators. Promoting alignment between local cultural values and Islamic law is essential for navigating patriarchal and matriarchal systems. Continuous focus on these principles is vital for ensuring the meaningful contributions of Acehnese female legislators and empowering future generations of women.